Nutrient resorption in dominant species of forests in the 'Espinal Mesopotámico' (Argentina) - Mendoza, Carlos A; Turrión, M Belén; Aceñolaza, Pablo G; Gallardo, Juan F; Pando, Valentín (Bosque (Valdivia), 2017)
The resorption of nutrients of dominant species in a successional sequence of forests of the Argentinean Mesopotamian Espinal was studied for two years (2009-2010). The aim was to compare nutrient resorption (nitrogen, phosphorus, potassium, calcium, magnesium and sulphur) among species of the Fabaceae (Acacia caven, Prosopis affinis and Prosopis nigra with the capacity of biologically fixing the atmospheric nitrogen) and Celtidacea families (Celtis tala, without the capacity of biologically fixing the atmospheric nitrogen). Samples of mature leaves (collected in spring) and senescent leaves (collected in autumn) were chemically analyzed to determine nutrient concentration; afterwards, resorption rates were calculated (Rc7 and Rc2). It was found that the higher nitrogen resorption was associated with the inability of biologically fixing the atmospheric nitrogen, having both indexes a maximum nitrogen resorption in C. tala and a minimum in A. caven. On the contrary, the other elements (P, K, Ca, Mg and S) showed resorption differences in one of the indexes used, indicating a higher resorption in Fabaceae in contrast with Celtidaceae, associated with a higher foliar demand of these elements.